The relationship between malnutrition, diet quality and health-related quality of life among the elderly: A cross-sectional study - Gezer, Ceren; Yurt, Merve; Harmancioglu, Begum; Yildirim, Aysen; Elmas, Cemre (Mattioli 1885, 2020)
Introduction: This study aims to evaluate the relationship between malnutrition, diet quality and health-related quality of life among the elderly in Famagusta, Cyprus. Materials and Methods: This study was conducted with 279 individuals aged 65 and over who were living in Famagusta, Cyprus between February 2017 and May 2018. Data was collected via one-to-one interviews using the following evaluation forms. The Mini Nutritional Assessment (MNA) evaluated demographic characteristics, nutritional habits, 24-hour retrospective food consumption records and risk of malnutrition. The Medical Outcome Study Short Form (SF-36) evaluated quality of life. In addition, participants' body weight, height, waist, hip, mid-upper arm and calf circumferences were measured using appropriate techniques. Results: Of the participants, 5.4% had malnutrition, and 9.3% were at risk of malnutrition. Participants over the age of 85 had the highest risk of malnutrition (p<0.05). Males had a higher physical and mental quality of life and a lower risk of malnutrition than females (p<0.05). Those without a risk of malnutrition had a higher mental and physical quality of life than those with a risk of malnutrition (p<0.001). As diet quality increased, the physical quality of life increased. And as the quality of physical and mental life increased, the risk of malnutrition decreased (p<0.05). Conclusion: Increased age is associated with increased risk of malnutrition. Males have a lower risk of malnutrition than females. As the quality of diet increases, the physical quality of life increases. And as the quality of physical and mental life increases, the risk of malnutrition decreases. Planning further cross-sectional, longitudinal and intervention studies with larger sample sizes to evaluate other factors that affect the relationship between malnutrition, diet and health-related quality of life in the elderly, is significant in terms of developing preventive public health policies.
Keywords: malnutrition; diet; quality of life; elderly